1992
DOI: 10.3109/08958379209145301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Exposure to O3On Rats: Sequence of Epithelial and Inflammatory Changes in the Distal Airways

Abstract: This study involves the analysis of the sequence of changes in lung epithelial permeability, free cells in the airways, prostaglandin E2 (PC€;J levels, polymorphonuclear leukocyte (PMN) flux, and alveolar lesions in rats exposed to 0.8 ppm ozone (03 for 3 h and then studied at 4-h intervals up to 24 h postexposure. Protein content of the bronchoalveolar lavage (BAL) increased immediately after O3 exposure and returned to control levels by 16 h postexposure. Albumin concentration in the BAL also increased with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Ã Po0:05 and ÃÃ Po0:01 compared with breathing air for 1 h. to 0.8 ppm ozone, permeability to 99m Tc-DTPA and BAL, it was suggested that the neutrophil influx occurred as a consequence of the increased permeability, rather than causing the increased permeability. 23 Ozone-induced permeability in rats, exposed to 0.8 ppm for 2 h, was inhibited by pretreatment with cyclophosphamide, FPL 55712 (a leukotriene D 4 antagonist) and indomethacin. 5 Neutrophils from ozone exposed rats have been shown to alter epithelial resistance in vitro, but only when stimulated with PMA or FMLP.…”
Section: Discussionmentioning
confidence: 97%
“…Ã Po0:05 and ÃÃ Po0:01 compared with breathing air for 1 h. to 0.8 ppm ozone, permeability to 99m Tc-DTPA and BAL, it was suggested that the neutrophil influx occurred as a consequence of the increased permeability, rather than causing the increased permeability. 23 Ozone-induced permeability in rats, exposed to 0.8 ppm for 2 h, was inhibited by pretreatment with cyclophosphamide, FPL 55712 (a leukotriene D 4 antagonist) and indomethacin. 5 Neutrophils from ozone exposed rats have been shown to alter epithelial resistance in vitro, but only when stimulated with PMA or FMLP.…”
Section: Discussionmentioning
confidence: 97%
“…Samples were collected during mouse exposures, and the impactor stages were extracted in distilled water. Ovalbumin extracted from the impactor stages was analyzed using a bicinchonicinic acid procedure (Bhalla and Young, 1992) with absorbance measured at 562 nm. Animals were sacrificed 1 day after the second antigen challenge.…”
Section: Antigen Sensitization Challenge and Exposure To Concentratmentioning
confidence: 99%
“…Epithelial permeability. Permeability of the nasal epithelium was measured at 1 h following the last exposure (Bhalla et al, 1986, Bhalla andYoung, 1992). Animals were anesthetized with 73 mg/kg sodium pentobarbital, polyethylene tubing (PE-90) was placed in the trachea, and a polyethylene catheter (P-10) was placed in the femoral artery.…”
Section: Respiratory Tract Clearancementioning
confidence: 99%
“…Lactate dehydrogenase was analyzed spectrophotometrically by enzymatic conversion of pyruvate to lactate in the presence of NADH (Sigma Chemical, St. Louis, MO). Albumin concentration was evaluated with an enzyme-linked immunosorbent assay (ELISA) as described by Bhalla and Young (1992).…”
Section: Broncho-alveolar Lavage and Pulmonary Macrophage Functionmentioning
confidence: 99%